Europe not for all? Romani Immigrants in Western European Countries - Talewicz-Kwiatkowska, Joanna (Journal of Applied Cultural Studies, 2015)
The study aims at an analysis of Romani immigrants’ position in Western European countries with a special emphasis on the selected countries’ policies. The author focuses on Romani immigrants in Italy and France, noting that as a result of the internal diversification of the Romani community, it is impossible to develop a single strategy and policy. Due to that fact, the author is of the opinion that it is necessary to follow a diversified approach which considers social and cultural contexts, as well as economic, geographic and legal issues.